A Scientometric Analysis of the 50 Most Cited Articles for Reconstruction of the Lower Extremity. (28th January 2019) - Mbaidjol, Zacharia; Rothenberger, Jens; Chetany, Rajesh
Abstract : Background . Lower extremity reconstruction has always been a challenge. Some of the published articles had a major impact on the field but are often not considered as classics because they have fewer citations. We therefore conducted a scientometric analysis of the most cited articles with a focus solely on the lower limb. Methods . A search was conducted on Medline, the Web of Science database, Google Scholar, and Scopus identifying articles relevant to reconstructive surgery of the lower limb. All journals were included with no time frames. Articles relating solely to orthopedics or vascular reconstruction were excluded. The number of citations obtained were then plotted and compared between the different search engines. The mean citation number was calculated by taking into consideration the total number of years since the article's first year of publication. Articles were then ranked and classified according to their authors, their years of publications, and their countries. They were furthermore categorized and analyzed. Results . Highly cited articles were easily retrieved with Google Scholar, mostly published in Plastic and Reconstructive Surgery ( n  = 37) and were mainly authored by American Medical Centers ( n  = 22). Fifty-four percent (54%) of these classic articles discussed the design of new flaps or were anatomical studies. Conclusions . We were not able to find a correlation between the year of citation and the number of citations. The citation pattern of a paper cannot be predicted, but a majority of highly cited article allowed the design of new reconstructive techniques.